La Performance De L'entreprise - Boustil, Zehaira (جامعة الوادي - University of Eloued, 2022)
Performance is a complex concept, its definition remains a difficult exercise given that it covers several meanings; it is a multidimensional concept, denoting ambiguities, which ultimately only makes sense in the context in which it is used. The objective of this article is to treat, at first, the conceptual framework of performance, through a reading grid moving from an unidimensional vision focused on the financial aspect (financial performance) to a multidimensional option ( global performance), while presenting its different dimensions, introducing new societal and environmental preoccupations for a responsible enterprise; then, examine the indicators of its measurement through the review of some explanatory models, and in conclusion, we try to present some propositions in order to establish pertinent strategies whish based on specific competencies enabling it to adapt to environmental turbulence and build a sustainableRésumé : La performance est un concept complexe, sa définition demeure un exercice difficile étant donné qu’il recouvre plusieurs acceptions ; c’est un concept multidimensionnel, dénotant des ambiguïtés, qui, en dernier lieu, ne prend de sens que dans le contexte dans lequel il est utilisé. L’objectif de ce présent article, est de traiter, en premier lieu, le cadre conceptuel de la performance, à travers une grille de lecture passant d’une vision unidimensionnelle axée sur l’aspect financier )performance financière) à une option multidimensionnelle (performance globale), tout en présentant ses différentes dimensions, introduisant de nouvelles préoccupations sociétales et environnementales pour une entreprise responsable; ensuite, examiner les indicateurs de sa mesure à travers la recension de quelques modéles explicatifs, et en guise de conclusion, ébaucher quelques propositions susceptibles d’ouvrir des pistes de réflexions pour l’élaboration des stratégies pertinentes reposant sur des compétences spécifiques lui permettant de s’adapter aux turbulences environnementales et de construire un avantage concurrentiel durable. competitive advantage.
Concepts Et Indicateurs De Mesure
مقال
Keywords: performance ; entreprise ; performance financière ; performance globale ; indicateur